A percepção da enfermagem frente a assistência prestada ao potencial doador de órgãos na morte encefálica - GONZAGA, Margareth Cordeiro (2021)
Introduction: Brain death (BD) is the complete and irreversible loss of brain functions, defined by the cessation of cortical and brainstem activities. Organ transplantation aims to save lives and also confer a better quality of life to transplanted patients. In Brazil, in 2019, 11,450 patients diagnosed with BD were classified as potential donors, but out of this total, only 3,768 were actual donors. Thus, it becomes relevant to the nursing team's performance against the potential donor so that he/she becomes an effective donor. Objective: The aim of this study was to understand the perception of the nursing team regarding the patient diagnosed with BD. Method: For this purpose, exploratory research with a qualitative approach was conducted in a hospital located in the northwest of Paraná, in the ICU sector, with professionals who work directly with critical patient care. For this, a semi-structured questionnaire containing discursive questions was applied. The data were analyzed using Bardin's content analysis method. Results: As a result of the results, three categories emerged, described as: understanding the assistance given to the potential donor, the difficulties in the family approach to the DP and the impact of the pandemic in the professionals' view. Conclusion: The assistance given to the patient with BD as a potential donor and to the family member is permeated by many difficulties, which leads to the need of implementing courses and training for professional qualification.